Ground-Based Microwave Radiometer Calibration: an Overview - Miacci,Marcelo (2018)
ABSTRACT This paper intends to briefly present some basic concepts on the microwave radiometry and radiometer calibration research in remote sensing applications and demonstrate results and analysis of the cryogenic calibration of a microwave ground-based radiometer currently deployed in scientific campaigns in Brazil. The equipment described in this text operates at 22 - 30 GHz and at 51 - 59 GHz frequency ranges and uses as the calibration standard a target cooled by liquid nitrogen. Since an accurate calibration (with observation errors below 0.5 K) is important to provide confidence in the retrieval of vertical temperature and humidity profiles, this work aims also to comment on some effects of the errors in calibration procedure on the atmospheric parameters of interest.